2021
DOI: 10.1093/mnras/stab099
|View full text |Cite
|
Sign up to set email alerts
|

Spectral signature of atmospheric winds in high-resolution transit observations

Abstract: The study of exoplanet atmospheres showed large diversity compared to the planets in our Solar system. Especially Jupiter-type exoplanets orbiting their host star in close orbits, the so-called hot and ultra-hot Jupiters, have been studied in detail due to their enhanced atmospheric signature. Due to their tidally locked status, the temperature difference between the day- and nightside triggers atmospheric winds that can lead to various fingerprints in the observations. Spatially resolved absorption lines duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…This would be in agreement with the shift detection of the hotspot east of the substellar point on 55 Cnc e detected by Demory et al ( 2016 ). Such a shift is usually driven by atmospheric circulation processes, including a significant amount of atmospheric mass (Showman & Polvani 2011 ;Miller-Ricci Kempton & Rauscher 2012 ;Keles 2021 ). Although we cannot rule out a heavy silicate-atmosphere existing below the presented altitude limits inferred in this work, with a median value of R ext = 1.9 × R P , or a deck of mineral clouds (Mahapatra et al 2017 ) that hide absorption signatures, this study showed that very high S/N data can deliver informative upper limits on the extension of the possibly existing silicate atmospheres probing deeply the atmospheres of terrestrial exoplanets.…”
Section: Discussion a N D C O N C L U S I O Nsupporting
confidence: 81%
“…This would be in agreement with the shift detection of the hotspot east of the substellar point on 55 Cnc e detected by Demory et al ( 2016 ). Such a shift is usually driven by atmospheric circulation processes, including a significant amount of atmospheric mass (Showman & Polvani 2011 ;Miller-Ricci Kempton & Rauscher 2012 ;Keles 2021 ). Although we cannot rule out a heavy silicate-atmosphere existing below the presented altitude limits inferred in this work, with a median value of R ext = 1.9 × R P , or a deck of mineral clouds (Mahapatra et al 2017 ) that hide absorption signatures, this study showed that very high S/N data can deliver informative upper limits on the extension of the possibly existing silicate atmospheres probing deeply the atmospheres of terrestrial exoplanets.…”
Section: Discussion a N D C O N C L U S I O Nsupporting
confidence: 81%
“…In high resolution, where individual spectral lines are resolved, the problem becomes even more intricate. This is because line shapes, depths and positions depend profoundly on the 3D thermal structure and chemical composition of the planet, as well as its wind profile and rotation (Miller-Ricci Kempton & Rauscher 2012;Showman et al 2013;Kempton et al 2014;Rauscher & Kempton 2014;Zhang et al 2017;Flowers et al 2019;Harada et al 2021;Seidel et al 2020;Beltz et al 2021;Keles 2021). Hence, comparing observational data to the wrong models may lead to wrong con-★ E-mail: joost.wardenier@physics.ox.ac.uk clusions about the nature of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%